Choroidopatia pełzająca – spektrum zmian na dnie oka w 3-letnim okresie obserwacji choroby - Wyrwicka, Anna; Jurowski, Piotr (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Serpiginous choroidopathy (SC) is classified as idiopathic chorioretinal disease. Atrophy of external retina comprising foveolar area and/ or submacular neovascularisation is a leading cause of visual acuity deterioration. A case report shows progression of fundus lesion in the course of SC during 3 years of follow up.